Pelibatan Dewan Perwakilan Rakyat dalam Pengisian Jabatan Hakim Agung dan Hakim Konstitusi - sri hastuti puspitasari (Fakultas Hukum Universitas Islam Indonesia, 2018)
One of the reasons to involve the House of Representatives to take the position of Chief Justice and Constitutional Judges after the amendment to the 1945 Constitution is the phenomenon of the House’s empowerment in the Indonesian constitutional system during the transition to democracy through the amendment. Such involvement can potentially cause problems, for example, the decisive authority of the House of Representatives in selecting the Chief Justice and constitutional judges, leading to politicization problem. This research formulates the following issues, first, the reasons for involving the House of Representatives in filling in the position of Chief Justice and Constitutional Judges. Second, whether the involvement is in accordance with the principle of separation of power as well as check and balance. This study is normative research with secondary data sources derived from legal materials, with conceptual, case, and statutory approaches. The results show that first, the involvement of the House of Representatives for Chief Justice and Constitutional Judges positions is part of the process of democracy beginning after the New Order transition period. Second, The involvement is also a deviationfrom the principle of separation of power, and such practice does not even reflect the principle of check and balance because the House of Representatives dominates all the selection processes.